Neodymium-Doped TiO2 with Anatase and Brookite Two Phases: Mechanism for Photocatalytic Activity Enhancement under Visible Light and the Role of Electron - Douga Nassoko; Yan-Fang Li; Jia-Lin Li; Xi Li; Ying Yu (International Journal of Photoenergy)
Titanium dioxide (TiO2) doped with neodymium (Nd), one rare earth element, has been synthesized by a sol-gel method for the photocatalytic degradation of rhodamine-B under visible light. The prepared samples are characterized by X-ray diffractometer, Raman spectroscopy, UV-Vis diffuse reflectance spectroscopy, X-ray photoelectron spectroscopy, and Brunauer-Emmett-Teller measurement. The results indicate that the prepared samples have anatase and brookite phases. Additionally, Nd as Nd3+ may enter into the lattice of TiO2 and the presence of Nd3+ substantially enhances the photocatalytic activity of TiO2 under visible light. In order to further explore the mechanism of photocatalytic degradation of organic pollutant, photoluminescence spectrometer and scavenger addition method have been employed. It is found that hydroxide radicals produced by Nd-doped TiO2 under visible light are one of reactive species for Rh-B degradation and photogenerated electrons are mainly responsible for the formation of the reactive species.